Energy Intensity and Productivity in Relation to Agriculture-Bangladesh Perspective (Journal of Bangladesh Academy of Sciences, 2010)
Results of the energy intensity and overall energetic efficiency show that total energy outputincreased from 69.87 to 82.08 GJha-1, with increasing commercial energy input from 17.94 to 27.10GJha-1 during 1990 to 2005. The corresponding increase in energy intensity was 45.67 to 54.47MJ/US$(2000). Energetic efficiency, calculated as the ratio of total output to input for differentcrops, using weight factor, decreased from 3.97 to 3.03. The energetic efficiency declines withincreasing energy input, and the result indicates that input energy increases faster compared toenergy output. The mechanization index increased from 64 to 78%. However, the main goal beingmaximization of the output per unit agricultural land, the estimated change in efficiency withincreasing input can play an important role in choosing the appropriate input for optimum output.Key words: Energy intensity; Productivity; AgricultureDOI: 10.3329/jbas.v34i1.5492Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 59-70, 2010